The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 1st Economics and Business International Conference 2017 (EBIC 2017) 2018
DOI: 10.2991/ebic-17.2018.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Servicescape And Customer Experience On Social Location Marketing (Case Study At Caf, In Medan)

Abstract: Nowadays, a cafe is becoming a trend and growing rapidly in Medan. There are numerous people spend their time to socializing in cafes is part of the current life style. Therefore, cafe owners compete in offering new cafe concept to attract customers. To gain competitiveness and attractiveness, cafe must possess the interesting servicescape and be providing good impression toward customers in a cafe. In the social media era, people can communicate and share their experience with other people easy. The interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The physical condition of the service environment experienced by customers also plays an essential role in shaping the service experience and strengthening (or reducing) customer satisfaction, especially for services at a high level of contact and involving humans in the process. Situmorang, Mulyono, & Azmi (2017) revealed that the research results show that Servicescape influences customer experience and social location marketing. That is, entrepreneurs or marketers must provide a unique servicescape (color, music, layout, aesthetics, seating, temperature, and cleanliness).…”
Section: Introductionmentioning
confidence: 78%
“…The physical condition of the service environment experienced by customers also plays an essential role in shaping the service experience and strengthening (or reducing) customer satisfaction, especially for services at a high level of contact and involving humans in the process. Situmorang, Mulyono, & Azmi (2017) revealed that the research results show that Servicescape influences customer experience and social location marketing. That is, entrepreneurs or marketers must provide a unique servicescape (color, music, layout, aesthetics, seating, temperature, and cleanliness).…”
Section: Introductionmentioning
confidence: 78%
“…According to Parasuraman et al (1988), there are five dimensions of SERVQUAL service quality that can be used to evaluate service quality: tangible, reliability, responsiveness, assurance, and empathy. Situmorang et al (2018) said that a servicescape is an organizational, physical facility used to influence consumers' feelings to be happy and have positive emotions. According to Gani et al (2022), a servicescape is a style and form of a physical environment consisting of several exterior elements such as information boards, parking lots, natural landscapes, and interior features such as design, layout, equipment, and decorations that customers can find.…”
Section: Service Qualitymentioning
confidence: 99%
“…failure was predicated on selecting the right location for any business [44]. Coffee shop owners are strategic about the location of coffee shops [68]. In addition to the physical location, the SBs also conveyed their decision for the interior décor of the coffee shops.…”
Section: Sb Comment Sb1mentioning
confidence: 99%
“…The SBs I interviewed conveyed that they needed to leverage the possibilities of social media in promoting their coffee shops. Through social media and social location marketing, customers can share their experiences and check in with others [68]. Instagram is based on visual content for example, posting of pictures, and Face-book has the capability for the customer to check into the coffee shop Check-ins show up in the feeds of that customer's Facebook friends, creating opportunities for people to see the business on Facebook.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%